2021
DOI: 10.1051/0004-6361/202140617
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of turbulent massive cores with ambipolar diffusion and hybrid radiative transfer

Abstract: Context. Massive stars form in magnetized and turbulent environments and are often located in stellar clusters. The accretion and outflows mechanisms associated with forming massive stars and the origin of the stellar multiplicity of their system are poorly understood. Aims. We study the effect of magnetic fields and turbulence on the accretion mechanism of massive protostars and their multiplicity. We also focus on disk formation as a prerequisite for outflow launching. Methods. We present a series of four ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 113 publications
2
34
2
Order By: Relevance
“…The observations presented here show this type of structure at smaller scales (<1000 au), which have been observed in disks of single systems (e.g., Maud et al 2019;Johnston et al 2020b). Simulations show that gravitational instabilities of the circumstellar disk can produce spirallike arms that can feed the protostar in episodic bursts of accretion (e.g., Meyer et al 2018;Mignon-Risse et al 2021;Riaz et al 2021). These simulations show overdensities with shapes similar to that of the continuum observations presented here and are predicted to be observable by ALMA at high resolution (Ahmadi et al 2019;Meyer et al 2019).…”
Section: Streamer Originsupporting
confidence: 64%
“…The observations presented here show this type of structure at smaller scales (<1000 au), which have been observed in disks of single systems (e.g., Maud et al 2019;Johnston et al 2020b). Simulations show that gravitational instabilities of the circumstellar disk can produce spirallike arms that can feed the protostar in episodic bursts of accretion (e.g., Meyer et al 2018;Mignon-Risse et al 2021;Riaz et al 2021). These simulations show overdensities with shapes similar to that of the continuum observations presented here and are predicted to be observable by ALMA at high resolution (Ahmadi et al 2019;Meyer et al 2019).…”
Section: Streamer Originsupporting
confidence: 64%
“…Riaz et al 2014, for ∼equal-mass low-mass binaries) and disk fragmentation (e.g. Mignon-Risse et al 2021, in which disk fragmentation is precipitated by the collision of extended spiral arms).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent magnetohydronamic (e.g. Mignon-Risse et al 2021) and hydrodynamic (e.g. Oliva & Kuiper 2020) models of the collapse of massive cores indicate that binaries form via disk rather than core fragmentation, with disk spiral arms playing an important role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the influence of magnetic fields reduces disk formation due to magnetic braking as shown in Figure 8, which shows thin density projections of the dense circumstellar material, as a function of primary stellar mass, that surround the primary star along its equatorial plane for runs ROFµ φ 2 (top row) and ROFWµ φ 2 (bottom row). Rosen & Krumholz (2020) showed that magnetic braking, which removes angular momentum from the infalling material as the core collapses inhibits the formation of a discernible accretion disk around the massive star, however higher resolution and non-ideal MHD effects such as ambipolar diffusion and Ohmic re-sistivity may reduce how much angular momentum is removed leading to smaller accretion disks than those produced when magnetic fields are not included (e.g., Zhao et al 2020;Mignon-Risse et al 2021;Commerçon et al 2021). Such effects are not explored in this work.…”
Section: Accretion Disk Formation and Evolutionmentioning
confidence: 99%